Which technique is suitable for management of acute myocardial infarction following coronary artery bypass surgery, rescue percutaneous coronary intervention or open heart surgery? A case-series studies - Sadeghi, Mohsen Mirmohammad; Hashemi, Mohammad; Rabbani, Majid; Gharipour, Mojgan; Nilfroush, Peyman; Majidi, Elham; Farahamand, Niloufar; Sadeghi, Poya Mirmohammad (Acta Biomedica Atenei Parmensis, 2014)
One of the serious complications followingcoronary artery bypass surgery is postoperative acute myocardial infarction commonly due to graft thrombosis, kinking, or spasm. Two recommended approaches for management of this event includeRescue percutaneous coronary intervention (PCI) and urgent open heart surgery. In the present case series, we described and compared early and long-term results of rescue PCI and reoperation in patients with three-vessel coronary artery disease undergoing CABG postoperatively and suffered acute myocardial infarction.